Agent based modeling and simulation of granuloma formation for the development of energy charging mechanism in Swarm Robots - Al Haek, Mohammed; Ismail , Amelia Ritahani; Nordin, Azlin (2014)
This paper presents an agent-based simulation of the processes involved in granuloma formation for the inspirations on the development of energy charging mechanism for swarm robotic systems. Granuloma formation is a process in which unwanted substances are removed by immune system. To better understand the components and the processes in granuloma formation, we simulate the process with agent based simulation and based on this simulation, analogous properties of the granuloma formation and swarm robotic systems are mapped accordingly based on their phases occurring during the development of granuloma.